Jekel's epidemiology, biostatistics, preventive medicine and public health - Katz, David L.; Jekel, James F. (Saunders, 2014)
Combining the disciplines of medical epidemiology, biostatistics, preventive medicine, and public health, this resource presents the information you need with a clinical focus, using real-life medical examples throughout.